2014
DOI: 10.1021/mz5002096
|View full text |Cite
|
Sign up to set email alerts
|

Threading of Ring Poly(ethylene oxide) Molecules by Linear Chains in the Melt

Abstract: We report results from an atomistic molecular dynamics simulation study of ring-linear poly(ethylene oxide) (PEO) melts followed by a topological reduction to ensembles of primitive paths and a detailed geometric analysis using vector calculus, which reveals considerable cyclic threading by the linear chains. The simulations have been conducted using ring-linear PEO blends of the same size, over a series of molecular lengths and compositions. For PEO melts characterized by molecular weight (MW) greater than 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
106
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 8 publications
(13 reference statements)
3
106
0
Order By: Relevance
“…Therefore, these threading effects that connect ring and linear chains constitute long lived entanglements which represent strong topological interactions that are capable of slowing down relaxation and chain mobility. 1,[34][35][36][37][38][39][40][41] In view of the above explained arguments, a threading effect of C-PCL by L-PCL chains reduces the spherulitic growth rates of ring PCL molecules, as shown in Fig. 6.…”
Section: Spherulitic Growth Rates Determined By Plommentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, these threading effects that connect ring and linear chains constitute long lived entanglements which represent strong topological interactions that are capable of slowing down relaxation and chain mobility. 1,[34][35][36][37][38][39][40][41] In view of the above explained arguments, a threading effect of C-PCL by L-PCL chains reduces the spherulitic growth rates of ring PCL molecules, as shown in Fig. 6.…”
Section: Spherulitic Growth Rates Determined By Plommentioning
confidence: 86%
“…6 Similar effects have been predicted by computer simulations. 1,[34][35][36][37][38][39][40][41] These studies have shown that cyclic molecules relax and diffuse more slowly than linear chains. Therefore, these threading effects that connect ring and linear chains constitute long lived entanglements which represent strong topological interactions that are capable of slowing down relaxation and chain mobility.…”
Section: Spherulitic Growth Rates Determined By Plommentioning
confidence: 99%
“…On the other hand, numerical and experimental findings (5,6) suggest that rings exhibit strong intercoil correlations, which have proved difficult to address in simplified theoretical models (9)(10)(11)(12). Because of this, there have been many recent attempts to rigorously characterize these interchains' interactions (13)(14)(15)(16), although a precise definition and unambiguous identification of these "threadings" in concentrated solutions of rings remains elusive. The primary reason for this is that the rings are assumed to remain strictly topologically unlinked from one another throughout if synthesized in this state.…”
mentioning
confidence: 99%
“…Phenomena in which topological effects play a role include the Quantum Hall effect [1], superconductivity [2], topological insulators [3], spin liquids [4], and defect behavior in crystals [5]. Due to the variety of and control over their connectivity, polymers are particularly interesting for exploring topological effects on physical properties, including polymer rheology [6][7][8][9] and thermodynamics [10][11][12][13][14][15][16][17][18]. In particular, polymer melts containing cyclic or long-branched chains have rheology and chain dynamics [13] that can differ dramatically with architecture and are different from those of linear analogs.…”
mentioning
confidence: 99%